An Analysis of Discipline and Personality in Blended Environments - Chan Chang Tik (The Canadian Network for Innovation in Education (CNIE), 2020)
The purpose of the study is to investigate the interaction between discipline and personality in a blended classroom using the community of inquiry model. To this end, a factorial ANOVA is used to determine the main effects of the high and low of each personality trait as well as the four different clusters of discipline on the presences. The study used a non-experimental design to gather data. A total of 12 lecturers and 408 students from three institutions were involved. The results indicate that there is a significant difference in teaching presence between the hard-applied and hard-pure as well as the hard-applied and soft-pure disciplines only for the conscientiousness personality. Correspondingly, there is a significant difference in social presence between the hard-applied and soft-pure disciplines across all the five personality traits. However, there is no significant difference in cognitive presence for all the discipline clusters across all the personality traits.